The reforms policy of general governor Yves Chataigneau in Algeria since 08th September 1944 to 11 th February 1948; The last chance of assimilation policy! - MENGHOUR , Ahmed (The Algerian Historical Journal, 2026)
This research attempts to go through some of the reform policy aspects that the Governor "Yves Chataigneau" wanted to apply in Algeria since 1944, and to examine the extent to which They were relevant to the implementation of the Trends and the general policy program of the French government, or being as a personal perception of the socialist general ruler! It is designed as well to measure the degree of success or failure. These reforms aim at changing the situation in Algeria to ensure the integration of Algeria with France, and to dismantle all bombs that were planted after the tragedies of May 08, 1945.